2012
DOI: 10.1080/17461391.2011.654270
|View full text |Cite
|
Sign up to set email alerts
|

The effects of air travel on performance measures of elite Australian rugby league players

Abstract: The current study explored the effects of short haul air travel within the same country on elite Australian rugby league (RL) players (n=12) during two away and two home games of elite competition. Physiological tests of handgrip strength and leg power were assessed along with psychological tests and perceptions of leg soreness and tiredness on the day before the game (Time 1 and Time 2) and on game day (Time 3). Game statistics of tackles and metres gained were assessed for the games analysed. Significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
(38 reference statements)
1
29
1
Order By: Relevance
“…Previous research suggests that conditions during air travel, particularly the prolonged exposure to mild hypoxia and cramped conditions, may temporarily augment perceptual fatigue 12,20,25 . Whilst this should not be discounted in the present study, results indicate that the aforementioned sleep disruption may have had a greater impact on perceptual responses and masked any temporary travel fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that conditions during air travel, particularly the prolonged exposure to mild hypoxia and cramped conditions, may temporarily augment perceptual fatigue 12,20,25 . Whilst this should not be discounted in the present study, results indicate that the aforementioned sleep disruption may have had a greater impact on perceptual responses and masked any temporary travel fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no change in CMJ or intermittent‐sprint performance was identified following simulated DOM travel. To date, only one other investigation has reported the effects of domestic air travel on physical performance, highlighting no change in handgrip strength or leg power (McGuckin et al., ). However, given the limited information available, further research is required to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced physical performance (Reilly et al., ; Lemmer et al., ; Chapman et al., ), adverse changes in physiological variables, including sleep (Lemmer et al., ; Beaumont et al., ; Bullock et al., ), and exacerbated mood states, such as increased subjective fatigue (Reilly et al., ; Waterhouse et al., ) have been reported following international transmeridian air travel. Conversely, negligible effects of domestic air travel have been identified on these variables (Richmond et al., ; McGuckin et al., ). However, as yet, the integration of performance, physiological, and perceptual measures related to intermittent‐sprint activities, and thus, training and competition in team sports are yet to be obtained following either domestic or international air travel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Travel fatigue is a complex summation of physiologic, psychologic, and environmental factors that accrue during an individual trip, such as prolonged exposure to mild hypoxia and cramped conditions with restricted activity [110,111]. Several studies have assessed the acute effects of short-haul air travel without crossing time zones (total travel time between 3-5 h) on performance and perceptual measures among team sport players [101,110,112]. Globally, results showed that travel has no effect on indicators of performance (i.e.…”
Section: Travelmentioning
confidence: 99%